1965
DOI: 10.1071/bi9650235
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Retranslocation in Seedlings of Hordeum Vulgare

Abstract: SummaryMeasurements have been made both on the uptake of potassium and potassium isotope from a nutrient solution and their redistribution within barley plants. During the experimental period the seedlings had three leaves which represented different stages in leaf development, i.e. from the mature to the rapidly developing stage.The results showed that substantial retranslocation of potassium within the plant took place. Translocation was most evident in the mature leaf which exported at least 1·6 Wequiv. per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

1966
1966
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…(This difference is due to translocation of potassium in the phloem from old to younger leaves.) However, the ratio of potassium to sodium in the shoot as a whole remains constant despite these differences between leaves (Pitman 1965a;Greenway and Pitman 1965). In barley seedlings the shoot thus behaves as a whole organ.…”
Section: Discussion (A) Regulation Of Uptake To the Shootmentioning
confidence: 99%
See 2 more Smart Citations
“…(This difference is due to translocation of potassium in the phloem from old to younger leaves.) However, the ratio of potassium to sodium in the shoot as a whole remains constant despite these differences between leaves (Pitman 1965a;Greenway and Pitman 1965). In barley seedlings the shoot thus behaves as a whole organ.…”
Section: Discussion (A) Regulation Of Uptake To the Shootmentioning
confidence: 99%
“…The level of potassium in the leaf cells is assumed to be maintained by active transport from the free space. The leaf as a whole receives ions from the xylem and can export potassium (preferentially to sodium) in the phloem, mainly to younger leaves (Greenway and Pitman 1965), but also to the roots. The level of ions in the free space of the leaves will be determined by the balance between these three processes (see also Robinson 1971).…”
Section: Discussion (A) Regulation Of Uptake To the Shootmentioning
confidence: 99%
See 1 more Smart Citation
“…Seedlings were grown on culture solutions which were basically the sarpe as described in previous publications (Pitman 1965a(Pitman , 1965bGreenway and Pitman 1965). The solutions were modified by varying levels of Ca(NOah and MgS04; the concentrations used in each experiment are given in the text and "a solution containing 10 m-equiv/l Ca(NOah" means a culture solution with all other nutrients at the standard level but with Ca(NOa)2 at 10 m-equiv/l.…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
“…It is well known that, many studies indicated that spraying some deciduous trees with Ca, K and CPPU either alone or in combination has been used successfully as an applicable mean for enhancing fruiting parameters through increasing fruit set, reducing fruit drop and improving both fruit characteristics and leaf nutritional status, which reflects finally on yield and quality, (Mansour et al (1986) on peach, Greenway and Pitman (1965) and Greene (1996) on apples, Bisal et al (1991) Kiwi fruits, Feng et al (1999), Marwad (2001) and Ben-Arie et al (2008) on seedless and seeded grapes, Tzoutzoukou and Bonranis (1997) on apricot, Moon et al (2000), Guriguis et al(2003) and on pear trees and and Abd El-Fatah et al (2008) on persimmon trees).…”
mentioning
confidence: 99%